A Missiological study on the perspectives and function of prayer in the AICs - Moletsane, T.M.J. (North-West University (South-Africa), 2017)
No matter how diverse religions are, the fact of the matter is there is one common practice they all embrace and that is prayer. Hindus do it, Buddhists do it, Muslims do it Christians do it and the African Independent Churches (AIC) also known as African Indigenous Churches also pray (Masondo 2014:2). But even if prayer is a common practice in different religions, the Mainline Mission Churches (MMC) (started by the missionaries from Europe and America) in sub-Sahara Africa are experiencing a movement of its members from the mainline Christianity to the African Independent Churches (AIC) especially the Zion Christian Church (ZCC) for prayer requests in times of emergency. African members of the Mainline Mission Churches in times of emergency feel that their needs cannot be addressed by the Mainline Mission Churches (MMC). They then patronise the priest in the African Independent Churches (AIC) especially the Zion Christian Church (ZCC) of Bishop Barnabas Lekganyane because the African Independent Churches (AIC) are believed to serve the needs and the character of the African people. Therefore, Christian African members of the Mainline Mission Churches (MMC) turn to become members of the African Independent Churches (AIC) in moments of crises in their lives (Mercado 2004, 2005:105). This study will look at different aspects of prayer in culture. The Lord's Prayer as model for prayer, and the African traditional view on prayer and the view of prayer in other religions. This will be done from a missiological perspective on the function of prayer in the growing ministry of the AICs.
M.A (Missiology), North-West University, Mafikeng Campus
Keywords: The Lord’s Prayer; African Independent Church (AIC); Mainline Mission Churches (MMC); Zion Christian Church (ZCC)